Effect of work, nutritional stress and level of re-alimentation on the composition of compensatory gains in draught oxen - Nsahlai, I.V.; Yimegnuhal, A.; Talle, S.B.; Osuji, P.O. (2004)
Thirty Highland zebu oxen with a mean weight of 276 (SE ± 14.3) kg and about 6 years of age were blocked by weight into 5 groups of 6 oxen each and within groups allocated to 6 treatments. They worked for 51 days followed by 84 days recovery. Teff straw (Eragrostis tef) and lablab (Lablab purpureus) (TSL) were fed during work and intercropped maize (Zea mays)/lablab (MSL)hay plus wheat bran was fed during recovery. Treatment 1 (T1) composed of ad lib feeding throughout the experimental period (control). In T2, the oxen were fed at 0.8 times theirmaintenance energy equirement during the working period and fed ad lib during recovery. Oxen in T1 and T2 were not assigned to work. The animals in T3, T4, T5 and T6 were fed ad lib and subjected to work loads involving the pulling of a sledge weighing 27.3 ± 1.6 kg onto which a weight equivalent to 10 % of live weight (LWT) of each animal was placed. The oxen worked for 5 h a day and 6 days per week. During the recovery period, animals in T3, T4, T5 and T6 received 0.7, 0.8, 0.9 and 1 times their estimated ad libitum feed intake based on the actual measurementduring the workperiod,respectively. Feed intake, average daily gain (ADG), dry matter (DMI)and organic matter (OMI) and fat depletion and repletion were estimated for all animals during the working and recovery periods. Rectal temperature, pulse and respiration rates were also recorded during the working period. Workreduced dry matter intake by 1.2 kg/d and caused an average body weight loss of 272 g/d compared to the control (T1). The effect of work (T3, T4, T5,T6) and nutritional restriction (T2) on live-weight change was similar during the work period (p>0.05). Work had no effect on dry Matter digestibility (DMD) and organic matter digestibility (OMD) (p>0.05). However, improved DMD and OMD were observed in the nutritionally restricted groups. Rectal temperature increased by 0.76° C and 1.24° C after 2.5 h and 5 h of work, respectively. Pulse and respiration rates increased by 21.9 and 40.8 beats/min after 5 h of work, respectively. Empty body fat (EBF) was reduced by work and increased at the end of the recovery period but there were no differences among treatments (T3, T4, T5 and T6). Generally there was a similarity between utritional and work stressed groups in energy deficit and composition of compensatory gains. On average these animals gained 281 g/d than the control (T1) group at the same level of feeding during the recovery period. It was concluded that nutritional stress and work stress caused similar weight loss and that the optimum quantity of nutrient required for compensatory growth following an intermediate level of work stress is about 0.9 times ad lib feeding (T5).